The play as a therapeutic physical activity in the elderly (Revisión) (Revista científica Olimpia, 2020)
Due to the social importance of working with the elderly in Ecuador, a systematic review of the literature that includes their characteristics and the importance of play for this age group will establish the theoretical basis of this means of therapeutic physical activity. The aim of this work is to reveal the importance of the play as a means of therapeutic physical activity for older adults. For this purpose, it has been reviewed the databases: Dialnet and Google Academic, in addition to both classic and contemporary books, master and doctoral theses, as well as websites using the descriptors: games, therapeutic physical activity and older adults. Three basic thematic areas have been established for the review, the first one is directed to the topic: Older adults and their characteristics, the second one to The therapeutic physical activity, and the third one to The Game as a didactic means. In total, 40 specific references to the topics addressed have been analyzed (articles, books, thesis and websites). The main conclusion is that play as a tool in the practice of therapeutic physical activity is the least treated, so the research should be directed to exploit the potential of this medium.